Strategy for Increasing Competitiveness Through Green Digital Marketing in Sandal SMEs in Wedoro Village with SWOT and QSPM Analysis - Devi Susiati; Rizky Nurrochmad Ismail; Nur Ahlina Febriyati (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy, particularly in job creation and strengthening regional economies. One MSME center that contributes significantly is the sandal MSME in Wedoro Village, Waru District, Sidoarjo Regency, which has developed as a cottage industry for generations. However, in recent years, this MSME has faced challenges in the form of increased product competition, shifts in consumer behavior toward digital, and market demands for environmentally friendly products. This has led some MSMEs to persist with conventional marketing and not optimally utilize digital potential. This research aims to formulate a strategy to increase the competitiveness of the sandal MSME in Wedoro Village through an integrated, data-driven green digital marketing approach. The case study for this research was conducted on the Odiva MSME owned by Ms. Yuni, as a representative MSME that still survives with stable production capacity but faces limitations in digital marketing. Data collection was conducted through observation, interviews, questionnaires, and documentation studies. Data were analyzed using the Life Cycle Assessment (LCA) method to compare the environmental impacts of products and packaging. This was followed by a SWOT analysis to identify internal and external factors. These factors were then objectively prioritized using the QSPM to determine the best strategy based on relative attractiveness. The targeted outputs of this research include the development of alternative strategies to increase the competitiveness of sandal MSMEs based on green digital marketing, the creation of an official website as a medium for sustainable digital promotion and branding, and the publication of scientific articles in accredited national journals. The research findings are expected to provide practical contributions to partner MSMEs in Wedoro Village in expanding their market reach, enhancing the image of environmentally friendly products, and supporting business sustainability.